A study on relationship between earnings before tax, interest and operational cash flows with stockholders’ equity - Mohammad Reza karimi Torghabeh; Hossein Parsian; Amir Shams Kolookhi (Management Science Letters)
One of the primary economic issues is associated with optimum resource allocation in profitable investments with reasonable risk. For this purpose, performance measurement’s criteria are needed some of which emphasize cash flow variables and some others focus on information content of accounting profit. On this basis, this study examines the relationship between earnings before tax and interest and operational cash flows with stockholders’ return in Tehran Stock Exchange (TSE). In this regard, information asymmetry was also examined. To test hypotheses, multivariable regression and combined data method were used. The results showed that based on the information of 102 companies in stock market from 2004 to 2009, there was a positive and significant correlation between earnings before interest and tax and stock return in the companies. While, operational cash flow has no significant impact on stock return. Increasing information asymmetry, earnings before interest and tax has a positive and significant correlation with stockholders ’return; but operational cash flow has no significant effect on stockholders’ return. In other words, earnings before interest and tax have higher information content than operational cash flow.